Evolutionary directional asymmetry and shape variation in Diabrotica virgifera virgifera (Coleoptera: Chrysomelidae): an example using hind wings. (13th November 2013) - Benítez, Hugo A.; Lemic, Darija; Bažok, Renata; Gallardo‐Araya, Claudio M.; Mikac, Katarina M.
<x xml:space="preserve">Abstract</x> The western corn rootworm Diabrotica virgifera virgifera LeConte is a pest of maize in the USA and Europe and especially a problem in particular regions of Croatia. In the present study, patterns of variation in hind wing shape were examined. The first objective was to examine the influence of soil type on 10 populations of D. v. virgifera sampled from three regions in Croatia that differed according to edaphic factors and climate. The second objective was to investigate the potential evolutionary presence of directional asymmetry on hind wings. Geometric morphometrics was used to examine these objectives by quantifying the morphological variation within and among individuals and populations. Overall, D. v. virgifera hind wing shape changed according to major soil type classifications in Croatia. The three hind wing morphotypes found varied because of basal radial vein differences, related to landmarks 1, 3, 7, and 14. The findings of the present study show that hind wing shape in D. v. virgifera can be used to differentiate populations based on edaphic factors and may have application as a monitoring tool in the integrated management of D. v. virgifera. In an evolutionary context, the presence of directional asymmetry in the hind wings of D. v. virgifera adds to the ever growing data on the evolution of insect wings. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 111, 110–118.